The Efficacy of DreamBuilder-Mediated TBLT in Enhancing English Proficiency: An Experimental Study on Women Entrepreneurs - Aqzhariady Khartha; Muthmainnah Bahri A. Bohang; Marhamah Marhamah; Heri Alfian (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2026)
English proficiency has become a critical determinant of business competitiveness for women entrepreneurs in Indonesia, yet existing programs rarely address their professional communication needs. This study investigated the effects of Task-Based Language Teaching (TBLT) through the DreamBuilder platform on the English proficiency of Indonesian women entrepreneurs in the Academy for Women Entrepreneurs (AWE) program, Makassar. A quasi-experimental mixed-methods design involved 40 participants in a TBLT group (n = 20) or Traditional instruction group (n = 20), with pre- and post-test scores, questionnaire, and interview data collected concurrently. The TBLT group demonstrated significantly greater proficiency gains (mean gain: 25.8 vs. 9.8 points; t(38) = 18.43, p < .001, Cohen’s d = 5.27). Participants rated task-profession relevance highly (M = 4.6) and reported increased daily professional English use post-intervention. Thematic analysis identified four facilitating factors such as task-profession alignment, platform flexibility, resource variety, and peer interaction, and four inhibiting factors such as technological barriers, delayed feedback, limited cultural relevance, and self-regulation challenges. Extending TBLT evidence to adult women entrepreneur learners through a purpose-built digital entrepreneurship platform constitutes the study’s primary novelty. Platform developers and policymakers are recommended to prioritize task localization, integrated feedback, and digital infrastructure investment to maximize TBLT effectiveness in comparable emerging economy contexts.